Conciliar diplomacy at the Council of Constance (1414-1418): unity and peacemaking in a world historical perspective : based on a true story - Stump, Phillip H. (Studies in the history of Christian traditions, 2024)
Phillip H. Stump, emeritus professor of history from Lynchburg College in Virginia, USA, has spent his academic career in research and writing focused on medieval reform movements and on the Council of Constance (1414-1418). He has especially endeavored to make the original sources on these topics more accessible to scholars and to make history more useful to students